Implementasi Pendidikan Karakter di MI Ma’arif Gesing - Sri Umaroh Dewi Pritami; Sri Haryanto; Salis Irvan Fuadi (Journal of Student Research, 2024)
This thesis aims to: (1) To find out how student character education is implemented at MI Ma'arif Gesing. (2) To find out the obstacles faced in implementing character education at MI Ma'arif Gesing. (3) To find out the solutions used to overcome obstacles in implementing character education at MI Ma'arif Gesing. This research uses descriptive qualitative research. Data collection techniques through observation, interviews and documentation. To obtain data from the research, researchers conducted interviews with the Head of Madrasah Ibtidaiyah Ma'arif Gesing, the Homeroom Teacher of Class II MI Ma'arif Gesing and the Homeroom Teacher of Class V MI Ma'arif Gesing. The results of research conducted by the author show that: (1) The implementation of character education through mujahadah activities at MI Ma'arif Gesing has gone well, using the habituation method. So that students get used to doing these activities. (2) The obstacles faced in implementing character education through mujahadah habituation activities at MI Ma'arif Gesing are the neglect of students, students who are difficult to condition, and the awareness of parents to accompany children's development. (3) The solution to overcome these obstacles is by providing the facilities needed by students.